The species composition of parasites of Bufo bufo (Amphibia: Bufonidae) in the surrounding area of Visimsky state nature biosphere reserve - A. V. Burakova; E. A. Baytimirova (Российский паразитологический журнал, 2019)
Objective of research: Characteristics of the species composition of parasites in common toad (Bufo bufo Linnaeus, 1758) inhabiting around Visimsky State Nature Biosphere Reserve. Materials and methods: 29 individuals of B. bufo were studied by the method of total helminthological autopsy. Catching of toads was carried out in the upstream flow of the Sulem River in the buffer zone of the Visimskiy Reserve during the reproduction period. Results and discussion: The species composition of parasites of B. bufo inhabiting Visimsky Biosphere Reserve (the upper Sulem river) has been studied for the first time. 5 parasite species were detected: Nematoda - Oswaldocruzia filiformis (Goeze, 1782), Neoraillietnema praeputiale (Skrjabin, 1916), Cosmocerca ornata (Dujardin, 1845), Rhabdias bufonis (Schrank, 1788) and 1 protozoa Opalinatea - Opalina ranarum (Purkinje et Valentin, 1835). The extensity of infection (EI) of common toads with helminths was 100 %, the index of abundance 47 %; protozoa infections 4 % and 0,45, respectively. Two nematode species O. filiformis (EI 100 %, index of abundance 27,8%) and R. bufonis (EI 89,7 %, index of abundance 13,3) dominated. In B. bufo selected for investigation no trematodes were found likely due to the «marriage post».